Pengaruh Kompetensi, Pelatihan dan Pengembangan Karir Terhadap Kinerja Karyawan - Muhammad Dedi Syahputra; Hasrudy Tanjung (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2020)
The purpose of this study was to determine the effect partially and simultaneously competence, training and career development on employee performance at PT. Angkasa Pura II (Persero) Kualanamu Branch Office. This study uses an associative approach, which is research conducted to determine the effect or relationship between the independent variable and the dependent variable. The population and sample in this study were employees of the Electrical And Mechanical Facility Division at PT. Angkasa Pura II (Persero) Kualanamu Branch Office, amounting to 60 people. The data collection technique used a questionnaire, while the data analysis used multiple linear regression analysis. The results showed that partially competence has a significant effect on employee performance. Partially training does not have a significant effect on employee performance. Partially career development has a significant influence on employee performance. And simultaneously competence, training and career development have a significant influence on employee performance at PT. Angkasa Pura II (Persero) Kualanamu Branch Office.